Investigation of Inlet Guide Vane Efficiency in Centrifugal Compressors for the Turbo Refrigeration Machines - Danilishin A.M.; Kozhukhov Y. V.; Fateeva E.S.; Aksenov A.A. (Problems of the Regional Energetics, 2025)
The article investigates the influence of geometric parameters of inlet guide vanes (IGVs), including blade profiling and design features, on their operational efficiency. IGVs are widely used in centrifu-gal compressors of turbo-refrigeration machines with various refrigerants to control compressor per-formance by adjusting flow swirl at the impeller inlet. The purpose of the study was to determine the effect of the shape and angle of curvature of the IGV blade profile on its effectiveness when cre-ating a flow swirl at the inlet to the impeller. The study provides theoretical foundations of how in-let swirl affects the aerodynamic characteristics of centrifugal compressor stages. The research method was numerical optimization by computational gas dynamics of the IGV blade profile. The computational domain for numerical experiments consisted of an axial inlet duct with IGV, a mixed-flow impeller, and a vaneless diffuser. Simulations were performed using ideal air as the working fluid under specified inlet atmospheric pressure and outlet mass flow conditions. Approximately 120 IGV flow path configurations were analyzed at four different vane positions. Performance character-istics were derived from numerical simulations, including IGV loss coefficients as functions of di-mensionless geometric parameters and blade shapes. The study established correlations between IGV design variants and performance characteristics, enabling the development of optimal design recommendations. The most significant finding reveals how IGV blade curvature angle critically affects swirl generation efficiency at the impeller inlet. These results contribute to improved efficiency of centrifugal compressors with IGVs in turbo-refrigeration machines using various refrigerants.